Analisis Laporan Keuangan PT. Darya Varia Laboratoria Tbk Tahun 2019-2022 - Mansurudin Mansurudin; Herlina Littu; Joelianti Dwi Supraptiningsih (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
In early 2020 Covid 19 entered Indonesia and had a lot of impact on the country's economy. But on the other hand, companies are still required to continue to have good company performance amid the Pandemic that has hit the whole world. This study aims to determine the company's performance assessed by financial ratio analysis at PT Darya Varia Laboratories in 2019 to 2022. The research method used is Qualitative method by measuring the ratio of liquidity, solvency, activity and profitability. Based on the research results, the liquidity ratio in 2019-2022 is in good condition, this can be seen from the Current Ratio and Quick Ratio above industry standards. Based on the solvency ratio in 2019-2022 shows unfavorable results, seen from the average Debt to Asset and Equty Ratio below the industry standard average. Based on the profitability ratio in 2019-2022, it shows a poor value, seen from the Net Profit Margin, ROI and ROE, the 4-year average is below the industry standard average. Meanwhile, based on the activity ratio in 2019-2022, it is quite good from the point of view of activity and asset turnover is quite good because the scale level of asset turnover shows an increase.